The sensory ecology of primate food perception, revisited. Issue 6 (15th December 2022) - Veilleux, Carrie C.; Dominy, Nathaniel J.; Melin, Amanda D.
Abstract: Twenty years ago, Dominy and colleagues published "The sensory ecology of primate food perception, " an impactful review that brought new perspectives to understanding primate foraging adaptations. Their review synthesized information on primate senses and explored how senses informed feeding behavior. Research on primate sensory ecology has seen explosive growth in the last two decades. Here, we revisit this important topic, focusing on the numerous new discoveries and lines of innovative research. We begin by reviewing each of the five traditionally recognized senses involved in foraging: audition, olfaction, vision, touch, and taste. For each sense, we provide an overview of sensory function and comparative ecology, comment on the state of knowledge at the time of the original review, and highlight advancements and lingering gaps in knowledge. Next, we provide an outline for creative, multidisciplinary, and innovative future research programs that we anticipate will generate exciting new discoveries in the next two decades.